IMPROVING STUDENTS™ ACHIEVEMENT IN READING COMPREHENSION THROUGH TEAM PAIR SOLO - Rambe, Iqbal Faisal; Siregar, Masitowarni - (Universitas Negeri Medan, 2014)
ABSTRACT This study attempts to improve students™ achievement in reading comprehension through team pair solo. This study was conducted by using classroom action research. The subject of this research was class VIII2 MTs Al-jihad which consisted of 41 students. The research was conducted in two cycles, cycle I consisted of four meetings and cycle II consisted of two meetings. The instruments for collecting data were quantitative data (reading comprehension test) and qualitative data (diary notes, observation sheet, and questionnaire sheet). Based on reading comprehension scores, students™ score kept improving in every reading comprehension test. Based on diary notes, observation sheet, and questionnaire sheet, it was found that the teaching-learning process ran well. The students were active, interested, and enthusiastic in reading. The result of the research showed that team pair solo significantly improved students™ achievement in reading comprehension. Key Words: reading, reading comprehension, team pair solo